PENINGKATAN MOTIVASI BELAJAR IPA SISWA KELAS V SD NEGERI 16 CELLU MELALUI PENERAPAN MODEL PEMBELAJARAN GUIDED NOTE TAKING - Sudarto, Sudarto; Satriani DH; Nurul Hazizah (Bajang Institute, 2024)
This research is a Classroom Action Research which aims to see the increasing of science learning motivation for the 5th Grade Students at SD Negeri 16 Cellu through the application of the Guided Note Taking Learning Model. This research was carried out over two cycles and each cycle was held in two meetings through four stages, namely planning, implementation, observation and reflection. The focus of this research is the application of the guided note taking learning model by teachers and student learning motivation. The subjects of this research were 18 of the 5th Grade students at SD Negeri 16 Cellu. The data analysis technique used in this research is a quantitative descriptive. The results of the research showed that the percentage increasing in the number of students whose motivation to learn science increased from cycle 1 to cycle 2 was 83.33%. Thus, it can be concluded that the application of the Guided Note Taking learning model can increase the science learning motivation of th 5th Grade students at SD Negeri 16 Cellu